2020
DOI: 10.1007/s00423-020-01962-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative leukocytosis and the resection severity index are independent risk factors for survival in patients with intrahepatic cholangiocarcinoma

Abstract: Purpose The incidence of intrahepatic cholangiocarcinoma is increasing worldwide. Despite advances in surgical and non-surgical treatment, reported outcomes are still poor and surgical resection remains to be the only chance for long-term survival of affected patients. The identification and validation of prognostic factors and scores, such as the recently introduced resection severity index, for postoperative morbidity and mortality are essential to facilitate optimal therapeutic regimens. Methods This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Recently, inflammation-based biomarkers have been shown to have prognostic value in patients with ICC [ 19 ]. Accordingly, we previously identified preoperative leukocytosis as an independent risk factor for survival after resection of ICC and proposed malnutrition and dehydration, cholangitis due to cholestasis, as well as a systemic reaction to a more aggressive tumor biology as explanations for our findings [ 5 ]. In line with these results, we observed significantly lower levels of preoperative leukocyte concentrations in patients undergoing resection of “very early” ICC.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, inflammation-based biomarkers have been shown to have prognostic value in patients with ICC [ 19 ]. Accordingly, we previously identified preoperative leukocytosis as an independent risk factor for survival after resection of ICC and proposed malnutrition and dehydration, cholangitis due to cholestasis, as well as a systemic reaction to a more aggressive tumor biology as explanations for our findings [ 5 ]. In line with these results, we observed significantly lower levels of preoperative leukocyte concentrations in patients undergoing resection of “very early” ICC.…”
Section: Discussionmentioning
confidence: 88%
“…Recent epidemiological data revealed a rising incidence; however, ICC remains a rarity, especially compared to hepatocellular carcinoma [ 2 ]. Although there is a lack of large clinical studies to identify patients, which benefit most from surgical resections, several prognostic factors for postoperative survival have been identified in the past, including multifocality, vascular invasion, lymph node involvement, and type of liver resection [ 3 , 4 , 5 , 6 , 7 ]. The tumor diameter itself as a prognostic factor has been a matter of debate: while the first staging system of the American Joint Committee on Cancer (AJCC) did not include tumor size, the 8th edition of the AJCC(/UICC) defines stage IA and IB depending on a maximum tumor size of 5 cm [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding abnormal preoperative laboratory evaluations, leukocytosis is long associated with perioperative complications, morbidity and mortality in colorectal, hepatic, ovarian and cervical disc surgeries. 34 , 35 , 36 , 37 Likewise preoperative elevated CRP is associated with higher morbidity and mortality in abdominal and thoracic cancer surgical patients. 38 There is scant evidence on the possible role of preoperative lymphopenia on postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that preoperative leukocytosis was common and correlates with poor pathological and survival outcomes in endometrial carcinoma patients 23 . A study showed that preoperative leukocytosis and the resection severity index were independent risk factors for survival in patients with intrahepatic cholangiocarcinoma 24 . Cancer patients with acute venous thromboembolism and elevated WBC count had an increased incidence of VTE recurrences, major bleeding, or death 25 .…”
Section: Discussionmentioning
confidence: 99%